PENDIDIK DAN PESERTA DIDIK DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Ramli, Hj. Efni (AL-ISHLAH: Jurnal Pendidikan, 2016)
Education can be interpreted as an attempt by adults to make a difference for children at every stage of their development. Teachers and Students are the major component in education.  In terms of education, especially for children, Islam has its own views. It can be seen from Fitrah concept. Fitrah is the basic element that human being have. It means human being is a good person that can be shaped according to instruction